Non-equilibrium solvation dynamics: results beyond linear response theory. (1st December 2020) - Choudhury, Sayantani; Patra, Aniket; Pathak, Arup Kumar; Samanta, Alok Kumar
Abstract : Optically controlled non-equilibrium solvation dynamics in condensed phase have been studied extensively both experimentally and theoretically. The main drawback of linear response theory (LRT) and other existing theories is that they are unable to elucidate the dependence of non-equilibrium solvation time correlation function, S ( t ), on the excitation wavelength, as observed in the experiment. In order to explain the experimental observation, we first develop a kinetic equation in 1D solvation coordinate (SC) space and then we propose a new perturbative method to derive an analytical expression for S ( t ) for an anharmonic potential in SC space. We observe from the result of S ( t ) that the calculated results of the same depend strongly on the innumerable optical states through excitation wavelength, when the potential is anharmonic in SC space, indicating the breakdown of LRT. We have shown that both excitation wavelength and rotational relaxation time carry the information of micro-heterogeneity. Another significant aspect of our work is that the analytical expression obtained for S ( t ) corresponding to the anharmonic potential decays multi-exponentially, whereas S ( t ) decays single exponentially for a harmonic potential. More significantly, the calculated results for S ( t ) are found to be in excellent agreement with the available experimental results for the heterogeneous system. GRAPHICAL ABSTRACT: